Blood group‐related antigen Ley on human platelets and its involvement in platelet aggregation via a possible interaction with CD61. Issue 9 (5th August 2020) - Zhu, Huijun; Ma, Qinqin; Li, Ruishu; Fu, Min; Lu, Ping
Abstract: Background: The Le y antigen is a carbohydrate chain belonging to the ABH‐Lewis blood group family. Le y has been reported to be present on red blood cells (RBCs) and granulocytes, but its distribution and function in platelets remain unknown. There are a variety of glycoproteins on platelets, which may carry the Le y antigen. This study aims to investigate the expression pattern and the function of Le y in human platelets. Study design and methods: Flow cytometry, Western blot, and immunofluorescence assays were performed to determine Le y expression on human platelets. ADP (1.25‐10 μM) and thrombin (0.05‐1 IU/mL) were used to activate platelets in the presence or absence of prostaglandin E1 (PGE1) and the Le y expression was evaluated again by flow cytometry. Blockade was performed with an anti‐Le y monoclonal antibody to verify the role of this epitope in platelet function. Finally, coimmunoprecipitation was performed to identify glycoproteins associated with Le y . Results: Le y was expressed on human platelets independent of ABO blood type. Le y expression was decreased in a dose‐dependent manner after activation with either ADP or thrombin, and this effect could be partially reversed by PGE1. Anti‐ Le y mAb treatment increased alpha‐granule release and neutralized the inhibitory effect of the anti‐CD61 antibody on platelet aggregation. In addition, Le y was proven to interact and colocalize with CD61. Conclusions: These results demonstrate nondifferential expression of Le y in platelets of different ABO blood types and suggest the involvement of Le y in platelet function, possibly via interaction with CD61.